THE INFLUENCE OF THE USE OF FINTECH PAYMENT ON THE FINANCIAL MANAGEMENT OF STUDENTS OF THE KRISTEN INDONESIA UNIVERSITY OF TORAJA AT THE FACULTY OF ECONOMICS MANAGEMENT STUDY PROGRAM 2020-2023 - Greis Patanggu, Auldri; Sriati said, Grace; Lisa Matasik, Ade (Universitas Islam Lamongan, 2024)
The aim of this research is to determine the effect of using fintech payments on the financial management of students at the Indonesian Christian University of Toraja. Quantitative research is the method used. Indonesian Christian University Toraja, Faculty of Economics, Management Study Program class 2020-2023 has 1,737 students. 100 people who used the Slovin formula were used as research samples. Primary data and secondary data were used, and data was collected using a questionnaire using the cost method, which was then processed using SPSS software. Instrument testing, classical assumption testing, simple linear regression analysis, and hypothesis testing are the data analysis techniques used in this research. At a significance level of 5%, it shows that the fintech payment variable has a positive but not significant effect. As shown by the tcount value of 1.679 which is higher than the ttable value of 1.661 with a significance level of 0.96 which is greater than 0.05, the fintecj payment variable has a positive but not significant effect on student financial management